Enhanced emissions of floral volatiles by Diplotaxis erucoides (L.) in response to folivory and florivory by Pieris brassicae (L.). (December 2015) - Farré-Armengol, Gerard; Filella, Iolanda; Llusia, Joan; Primante, Clara; Peñuelas, Josep
Abstract: The main function of floral emissions of volatile organic compounds (VOCs) in entomophilous plants is to attract pollinators. Floral blends, however, can also contain volatile compounds with defensive functions. These defensive volatiles are specifically emitted when plants are attacked by pathogens or herbivores. We characterized the changes in the floral emissions of Diplotaxis erucoides induced by folivory and florivory by Pieris brassicae . Plants were continually subjected to folivory, florivory and folivory  +  florivory treatments for two days. We measured floral emissions with proton transfer reaction/mass spectroscopy (PTR-MS) at different times during the application of the treatments. The emissions of methanol, ethyl acetate and another compound, likely 3-butenenitrile, increased significantly in response to florivory. Methanol and 3-butenenitrile increased 2.4- and 26-fold, respectively, in response to the florivory treatment. Methanol, 3-butenenitrile and ethyl acetate increased 3-, 100- and 9-fold, respectively, in response to the folivory  +  florivory treatment. Folivory alone had no detectable effect on floral emissions. All VOC emissions began immediately after attack, with no evidence of delayed induction in any of the treatments. Folivory and florivory had a synergistic effect when applied together, which strengthened the defensive response when the attack was extended to the entire plant. Highlights: We monitored the floral volatile emissions of herbivore-attacked plants with PTR-MS. Folivory alone did not cause any detectable changes in floral volatile emissions. Florivory caused immediate significant increases of few defensive floral volatiles. Folivory and florivory showed a synergistic effect enhancing the defensive respose.